Students and Supervisors’ Evaluation of Online International Doctoral Supervision - Salinas, Jesús (2018)
This research presents the initial results of a study on the processes of online PhD supervision in the Education Sciences field. Remote mentoring and supervision bring new problems to the delivery of high-level doctoral studies with a widely dispersed base of mature, part-time, international students. These processes are analyzed by taking into account the supervision dynamics, the communication and support systems used, the activity space developed, and the tools used. For this exploratory study, we opted for a semi-structured interview; open ended at first, but to which some closed questions were added (especially questions to order or statements to evaluate). Twenty-six supervisors and students were interviewed, affording a view from both sides, so as to better understand the process and its difficulties. A classification system was set up afterwards, using notes taken on the spot in the interviews, and, later on, the categories were applied to the interview transcripts. Key elements have been identified, in which to intervene to improve the process. By taking into account the supervisors’ and students’ points of view, a certain coincidence could be observed when identifying such elements, both in relation to the style of supervision and support to the process, as well as to the dynamics, or susceptible tools and applications to improve the process; although both groups do not attribute the same value.